Principle-centered leadership - Covey, Stephen R. (New York Summit Books)
In this guidedbook to personal fullfilment and professional success through "principle centered Leadership" the author of the best selling The 7 Habits of Highly Effective People invites readers to center their lives and leadership around timeless principles. He shows how no person or organisation can be content to stay where they are-how goals of excellence and total quality express an innate human need for progress in personal, interpersonal and organisational life.
Index.
Keywords: Leadership